A Systematic Review of Efficacy and Safety of Difelikefalin in Treating Pruritus in Hemodialysis Patients with Chronic Kidney Disease - Enggalhardjo, Muljani; Tumiwa, Gabriella Hilary; Khosasih, Yeshiza (Fakultas Kedokteran Universitas Pelita Harapan, 2024)
Background: Chronic Kidney Disease (CKD) is a type of kidney disease that gradual loss of kidney function over a period of months or years, usually more than 3 months. Uremic pruritus or chronic kidney disease-associated with CKD (CKD-aP) is a common complication that experienced by CKD patients especially for patients undergoing haemodialysis and it will negatively impact quality of life, for example depression, poor sleep quality, and miss dialysis sessions.Methods: Three online databases were used for the literature search: Science Direct, Embase, and PubMed. obtaining the information in January 2024. Using specific keywords, a comprehensive analysis of research articles was carried out. We examined the safety and effectiveness of difelikefalin in the management of pruritus in patients receiving hemodialysis who have chronic kidney disease.Result: Six studies were evaluated that met the criteria for inclusion. The efficacy of difelikefalin in all studies was examined by using WI-NRS as assessment tools for the primary outcome, and for the secondary outcome, skindex-10 or skindex-16 scoring, the 5-D itch scale, and the itch MOS (Medical Outcome Study) sleep disturbance scale were used. From all studies, difelikefalin in various dosages and routes (oral and intravenous) improved pruritus reduction in hemodialysis patients with CKD over placebo. However, in the majority of cases, difelikefalin caused a higher chance of experiencing adverse events than in the placebo group.Conclusions: All studies show a greater pruritus reduction in hemodialysis patients receiving therapy over placebo, with the optimal benefit-risk at 0.5 μg/kg of difelikefalin, despite unclear efficacy-dosage connections.